2022
DOI: 10.1021/acs.iecr.2c01689
|View full text |Cite
|
Sign up to set email alerts
|

Process Intensification of CO2 Desorption

Abstract: Anthropogenic climate change due to, among other causes, unhindered CO 2 emissions is a major concern worldwide. The postcombustion capture (PCC) process using a solvent, known as chemical absorption, is currently the most effective way to reduce CO 2 emissions from large point sources. However, high capital investment costs when using the conventional packed bed absorber/desorber technology and high energy requirements during solvent regeneration are the primary obstacles for its large-scale implementation. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 138 publications
0
5
0
Order By: Relevance
“…Performance of different technologies to intensify the desorption of CO 2 from solvents: PB, packed bed; i-PB, intensified packed bed; RPB, rotating packed bed; MW, microwave regeneration; US, ultrasound-assisted regeneration; MR, microreactor; MS, membrane stripping; CA, catalyst-aided solvent regeneration. Reproduced with permission from ref . Copyright 2022 American Chemical Society.…”
Section: Temeprature Swing Adsorption–desorptionmentioning
confidence: 99%
See 4 more Smart Citations
“…Performance of different technologies to intensify the desorption of CO 2 from solvents: PB, packed bed; i-PB, intensified packed bed; RPB, rotating packed bed; MW, microwave regeneration; US, ultrasound-assisted regeneration; MR, microreactor; MS, membrane stripping; CA, catalyst-aided solvent regeneration. Reproduced with permission from ref . Copyright 2022 American Chemical Society.…”
Section: Temeprature Swing Adsorption–desorptionmentioning
confidence: 99%
“…Figure shows the array of key technologies explored for CO 2 desorption intensification . Although the authors found that microreactors and membrane contactors are the most promising routes due to the enhanced CO 2 mass transfer coefficient that they provide, one critical drawback of these is their difficult scalability.…”
Section: Temeprature Swing Adsorption–desorptionmentioning
confidence: 99%
See 3 more Smart Citations